Neuroprotective and Neurotoxic Effects of Glial-Derived Exosomes - Oyarce, Karina; Cepeda, María Yamila; Lagos, Raúl; Garrido, Camila; Vega-Letter, Ana María; Garcia-Robles, María; Luz-Crawford, Patricia; Elizondo-Vega, Roberto (Frontiers in Cellular Neuroscience, 2022)
Exosomes derived from glial cells such as astrocytes, microglia, and oligodendrocytes can modulate cell communication in the brain and exert protective or neurotoxic effects on neurons, depending on the environmental context upon their release. Their isolation, characterization, and analysis under different conditions in vitro, in animal models and samples derived from patients has allowed to define the participation of other molecular mechanisms behind neuroinflammation and neurodegeneration spreading, and to propose their use as a potential diagnostic tool. Moreover, the discovery of specific molecular cargos, such as cytokines, membrane-bound and soluble proteins (neurotrophic factors, growth factors, misfolded proteins), miRNA and long-non-coding RNA, that are enriched in glial-derived exosomes with neuroprotective or damaging effects, or their inhibitors can now be tested as therapeutic tools. In this review we summarize the state of the art on how exosomes secretion by glia can affect neurons and other glia from the central nervous system in the context of neurodegeneration and neuroinflammation, but also, on how specific stress stimuli and pathological conditions can change the levels of exosome secretion and their properties.